Systematic Literature Review on the Fidelity of Maritime Simulator Training - Renan P. de Oliveira; Guido Carim Junior; Bruno Pereira; David Hunter; Jeanine Drummond; Marilyn Andre (MDPI AG, 2022)
The fidelity of a maritime simulator refers to how realistic the representation of a vessel and its environment look, behave, and feel in real life. Despite the benefits of using simulators in maritime training and education, there is a lack of understanding of different debates on whether higher levels of fidelity translate into better training outcomes. Therefore, to investigate and summarise what is known about maritime simulator fidelity, we conducted a systematic literature review on the maritime simulator-based training literature from 2005 to 2021. We performed bibliometric, authorship, and content analyses of thirty-six references, including white and grey literature. The results show that simulator fidelity is divided into physical and functional fidelity. While the former includes the ergonomics layout of the bridge, visual system, vessel manoeuvrability, and hydrographic modelling, the latter involves training program design, simulator session design, and the role of the instructor. The results reveal that there is no prevalent tradition in the literature, a low number of citations, and the references are dispersed among many publications, authors, and institutions. Despite the fact that the prevalence of studies employing high-fidelity simulators can positively impact training, most of the studies are based on subjective evaluation, if any evidence is provided, and were produced by Scandinavian and European institutions and researchers. To address these limitations, we propose a research agenda containing three recommendations.